An in vitro method for detecting infectious Cryptosporidium oocysts with cell culture. - Slifko, T R (1997)
Current assay methods to detect Cryptosporidium oocysts in water are generally not able to evaluate viability or infectivity. A method was developed for low-level detection of infective oocysts by using HCT-8 cells in culture as hosts to C. parvum reproductive stages. The infective foci were detected by labeling intracellular developmental stages of the parasite in an indirect-antibody assay with a primary antibody specific for reproductive stages and a secondary fluorescein isothiocyanate-conjugated antibody. The complete assay was named the focus detection method (FDM). The infectious foci (indicating that at least one of the four sporozoites released from a viable oocyst had infected a cell) were enumerated by epifluorescence microscopy and confirmed under Nomarski differential interference contrast microscopy. Time series experiments demonstrated that the autoreinfective life cycle in host HCT-8 cells began after 12 h of incubation. Through dilution studies, levels as low as one infectious oocyst were detected. The cell culture FDM compared well to other viability assays. Vital stains and excystation demonstrated that oocyst populations less than 1% viable (by vital dyes) and having a low sporozoite yield following excystation could not infect host cells. Until now, the water industry has relied on an oocyst detection method (under an information collection regulation) that is unable to determine viability. The quantifiable results of the cell culture method described demonstrate two important applications: (i) an infectivity assay that may be used in conjunction with current U.S. Environmental Protection Agency-mandated detection methodologies, and (ii) a method to evaluate oocyst infectivity in survival and disinfection studies.